Taxonomic revision of the Protopolybia picteti-emortualis species-group (Richards, 1978), with descriptions of two new species (Hymenoptera: Vespidae, Polistinae) - Dos Santos Junior, José N. A.; Silveira, Orlando T.; Carpenter, James M. (Zootaxa, 2020)
A taxonomic revision of the Protopolybia picteti-emortualis species-group now demonstrates that this group is possibly the largest in Protopolybia, comprising 15 species: P. eldinaris sp. nov.; P. djaneteae sp. nov.; P. cameranii (Zavattari 1906) = P. bella (Von Ihering 1903) syn. nov.; P. fulvotincta stat. rev.; P. biguttata, P. nitida, P. alvarengai, P. iheringi, P. perfulvula, P. steinbachi, P. wheeleri, P. rotundata, P. picteti, P. emortualis and P. duckei. Male and female genitalia are illustrated for P. biguttata Bequaert, P. bella, P. nitida, P. fulvotincta and P. picteti. New collection records and a new identification key are presented for this species-group.